Open and Closed Suction Ventilator Associated Pneumonia Prevention of Patient On Ventilator Installed - Supriandi Supriandi; Mardiyono Mardiyono; Made Desak Wenten Parwati (Jurnal Riset Kesehatan, 2014)
The objective of studys is to evaluate the differences of CPIS in applying CSS and OSS with oral hygiene chlorhexidine in critical patients with ventilators. In two hospitals in Semarang for two months. There were 30 subjects recruited by purposive sampling and divided in two groups equally (n=15). VAP was measured by CPIS on the third day after invasion. The interventions are OSS and oral hygiene with clorhexidine twice a day and CSS and oral hygiene with clorhexidine once a day during inserted ventilators. CPIS in the two groups were no significant difference. The OSS and oral hygiene with clorhexidine twice a day was similarly effective to the CSS and oral hygiene with clorhexidine once a day to prevent VAP in critical patients with ventilator (U=105; p=0,766). The application of the OSS with oral hygiene with clorhexidine twice a day is instead of the CSS with oral hygiene with clorhexidine once a day, which is more expensive to prevent VAP. Since there is no difference of CPIS in patients with OSS and CSS, at is recommended the use of SCC due to its lower cost compered to CSS method.